FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU DALAM MELAKSANAKAN PROSES BELAJAR MENGAJAR DI SMPN 5 TOMBOLA PAO KABUPATEN GOWA - Guntur Suryo Putro (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
Performance is an employee's success in completing the work. Teacher performance assessed on how to carry out the planning, implementation and evaluation of the learning process. As one istitusi education learning process is not optimal, in addition to the teacher who owned limited. The purpose of this research is to analyze the factors that affect the performance of teachers in implementing the learning process in SMPN5 Tombola Pao Gowa. This study is an observational study. The research method with cross sectional approach (cross-sectional). The population in this study is the total population of teachers in SMPN5 Tombola Pao Gowa. Ujii bivariate analysis with chi square and multivariate analysis with logistic regression test. Bivariate analysis showed that there is a relationship that siqnifikan between age (p = 0.002), education (p = 0.038), motivation (0,002), satisfaction (p = 0.023), perceived benefits (p = 0.020). Perception supervision (p = 0.023) with the performance of teachers in implementing the learning process. Multivariate analysis showed that there was an effect on the performance of teachers' motivation (p = 0.008) with Exp (b) = 25.670 and satisfaction variables on teacher performance (p = 0.057) with Exp (b) = 11.209. Suggestions can be recommended in this research is to increase the motivation of teachers in implementing the learning process followed by an increase in the satisfaction of teachers in implementing the learning process together, in addition to increasing the number of teachers with appropriate minimum academic qualification for the field of science.